Role of Augmented and Virtual Reality in Enhancing Effectiveness in Retailing: An Empirical Study (International Journal of Food and Nutritional Sciences, 2022)
Application of Augmented Reality (AR) and Virtual Reality (VR) are trending in marketing, particularly in retail industry for enhancement of shopping experience of consumers. Augmented Reality (AR) and Virtual Reality (VR) are emerging technological tools that are evolving continuously for surpassing the traditional methods of retailing. These collaborative technologies are enhancing the process of retailing as it offers a better and improved experience of shopping and impacting the preferences of customers towards retailers. There is a need for retailers to align their model of business to respond the altering patterns of traffic. Implementation of AR & VR is a substantial pattern that have got a far-reaching consideration and response over distinct sectors lately. Mainly, in retail sector, using computer-generated inventions in retail stores has the possibility of reshaping the experience of customers. Using augmented reality and virtual reality environment in retailing has been studied by many researchers as well as retailers, as it shows the world that increases an in-store experience for its customers. Moreover, it is highly suitable for retailers as well as for customers to advertise and examine the product. 217 respondents were considered in the study as a sample size. Mean and T-test was applied in the study to find the outcome.